2019
DOI: 10.1111/pedi.12854
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies between methods of continuous glucose monitoring in key metrics of glucose control in children with type 1 diabetes

Abstract: Objective: We aimed to compare glycemic control and variability parameters obtained from paired records of real-time continuous glucose monitoring (RT-CGM) and flash glucose monitoring (FGM). Methods: Ten Polish boys and 11 girls aged 15.3 ± 2.1 years with type 1 diabetes for 7.7 ± 4.5 years and glycated hemoglobin 7.35 ± 0.7% (57 ± 5 mmol/mol) were recruited between August 2017 and June 2018 and equipped with devices for RT-CGM (iPro2 system with Enlite electrodes) and FGM (FreeStyle Libre) for 1 week. Afterw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Third, patient characteristics, such as education level and socioeconomic status, dietary habits, and physical exercise, that may affect glycemic control were not assessed. Fourth, there may be significant difference in the CGM-derived metrics, including TIR and TBR, between the assessment with real-time CGM and that with isCGM [36]. Therefore, such glycemic markers cannot be directly compared in the discussion.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Third, patient characteristics, such as education level and socioeconomic status, dietary habits, and physical exercise, that may affect glycemic control were not assessed. Fourth, there may be significant difference in the CGM-derived metrics, including TIR and TBR, between the assessment with real-time CGM and that with isCGM [36]. Therefore, such glycemic markers cannot be directly compared in the discussion.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Therefore it is important to be able to rely on these parameters. However, it has already been shown that the time in glycemic ranges differs between CGM systems from different manufacturers worn in parallel and even between different sensors of the same CGM system [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Considering those devices had a greater data resolution of data transfer (5 minutes), it is encouraging to note that mean errors were comparable. Particularly given that flash glucose monitoring may obtain different estimates of important glycaemic variability compared to more traditional continuous monitoring devices (Michalak et al 2019).…”
Section: Main Findingsmentioning
confidence: 99%